THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) MODEL ON THE TOPIC OF FACTORS AFFECTING CHEMICAL EQUILIBRIUM - Sari, Maini Sari; Rusman, Rusman; Hanum, Latifah (Jurnal Ilmiah Mahasiswa Pendidikan Kimia, 2024)
The research titled "Implementation of the Problem Based Learning (PBL) Model on Factors Affecting Chemical Equilibrium" aims to describe student activities, analyze learning outcomes, and gather student responses to the application of the Problem Based Learning model. This research uses a descriptive type of study with a qualitative approach. The subjects of this research were 33 students of class XI IPAS 2 at SMA Negeri 2 Timang Gajah in the 2023/2024 academic year. The instruments used in this study included student activity observation sheets, learning outcome test questions, and student response questionnaires. The data analysis results showed that the average percentage of student activity was 79% in the first meeting and 93% in the second meeting. The average percentage of students achieving learning mastery was 80%, categorized as good. Student responses to the Problem Based Learning model indicated a positive reaction, with a percentage of 86%, categorized as very good. Based on the results of this study, it can be concluded that the implementation of the Problem Based Learning model can enhance student activity, ensure learning mastery, and receive very good feedback from students.